The secret garden - Howe, James, 1946-; Carpenter, Nancy; Burnett, Frances Hodgson, 1849-1924. (New York : Random House, 2004)
An abridged adaptation of the classic story of the ten-year-old orphan who goes to live in a lonely house on the Yorkshire moors, where she discovers an invalid cousin and the mysteries of a locked garden.
"A Stepping Stone book."
Originally published: 1993.
RL: 3.0.
Keywords: Orphans -- Fiction; Gardens -- Fiction; People with disabilities -- Fiction; Yorkshire (England) -- Fiction; England -- Fiction